Photocatalytic hydrogen production by biomimetic indium sulfide using Mimosa pudica leaves as template. (28th January 2019) - Carrasco-Jaim, Omar A.; Ahumada-Lazo, Ruben; Clark, Pip C.J.; Gómez-Solis, Christian; Fairclough, Simon M.; Haigh, Sarah J.; Leontiadou, Marina A.; Handrup, Karsten; Torres-Martínez, Leticia M.; Flavell, Wendy R.
Abstract: Biomimetic sulfur-deficient indium sulfide (In2.77 S4 ) was synthesized by a template-assisted hydrothermal method using leaves of Mimosa pudica as a template for the first time. The effect of this template in modifying the morphology of the semiconductor particles was determined by physicochemical characterization, revealing an increase in surface area, decrease in microsphere size and pore size and an increase in pore volume density in samples synthesized with the template. X-ray photoelectron spectroscopy (XPS) analysis showed the presence of organic sulfur (SO/SC/SH) and sulfur oxide species (SO2, SO3 2−, SO4 2− ) at the surface of the indium sulfide in samples synthesized with the template. Biomimetic indium sulfide also showed significant amounts of Fe introduced as a contaminant present on the Mimosa pudica leaves. The presence of these sulfur and iron species favors the photocatalytic activity for hydrogen production by their acting as a sacrificial reagent and promoting water oxidation on the surface of the templated particles, respectively. The photocatalytic hydrogen production rates over optimally-prepared biomimetic indium sulfide and indium sulfide synthesized without the organic template were 73 and 22 μmol g −1, respectively, indicating an improvement by a factor of three in the templated sample. Graphical abstract: Highlights: Synthesis of biomimetic In2.77 S4 using Mimosa pudica leaves for the first time. Photocatalytic hydrogen production threefold increased by the biomimetic In2.77 S4 . Enhanced photocatalytic activity attributed to morphology and surface composition. Efficient charge separation at surface reaction sites promotes water splitting. Functionalized photocatalyst inspired in nature for technological applications.